Dynamics and Control of Lorentz-Augmented Spacecraft Relative Motion - Yan, Ye.; Huang, Xu.; Yang, Yueneng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book develops a dynamical model of the orbital motion of Lorentz spacecraft in both unperturbed and J2-perturbed environments. It explicitly discusses three kinds of typical space missions involving relative orbital control: spacecraft hovering, rendezvous, and formation flying. Subsequently, it puts forward designs for both open-loop and closed-loop control schemes propelled or augmented by the geomagnetic Lorentz force. These control schemes are entirely novel and represent a significantly departure from previous approaches.
Introduction -- Dynamical Model of Lorentz-Augmented Orbital Motion -- Relative Navigation of Lorentz-Augmented Orbital Motion -- Dynamics and Control of Lorentz-Augmented Spacecraft Hovering -- Dynamics and Control of Lorentz-Augmented Spacecraft Rendezvous -- Dynamics and Control of Lorentz-Augmented Spacecraft Formation Flying.
Keywords: Aerospace engineering; Astronautics; Control engineering; System theory; Control theory; Aerospace Technology and Astronautics; Control and Systems Theory; Systems Theory, Control